REUSE INTENTION MODELS THROUGH CUSTOMER SATISFACTION DURING THE COVID-19 PANDEMIC: CASHBACK PROMOTION AND E-SERVICE QUALITY CASE STUDY: OVO ELECTRONIC MONEY IN JAKARTA - Hasyim, Umar; Hapzi Ali (Dinasti Publisher, 2022)
The purpose of this study was to analyze the relationship between the model of reuse intention through customer satisfaction during the covid-19 pandemic through cashback promotions and e-service quality. The study involved 190 users of the OVO application. Researchers used Partial Least Square (PLS) as a technique used to analyze measurements and structural models. The results of this library research are that: Cashback promotion and e-service quality have a positive and significant effect on customer satisfaction and OVO electronic money users in Jakarta; Cashback promotions and e-service quality have a positive and significant impact on the reuse intention of OVO electronic money services in Jakarta; There is a positive and significant effect of customer satisfaction on the reuse intention of OVO electronic money services in Jakarta; Customer satisfaction can mediate the effect between cashback promotions and reuse intention of OVO electronic money services in Jakarta; Customer satisfaction can mediate the influence between e-service quality and reuse intention of OVO electronic money services in Jakarta.